2021
DOI: 10.3389/fphar.2021.648769
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Plasma miRNA and Clinical/Hemodynamic Characteristics Provide Additional Predictive Information About Acute Pulmonary Thromboembolism, Chronic Thromboembolic Pulmonary Hypertension and Idiopathic Pulmonary Hypertension

Abstract: Idiopathic pulmonary artery hypertension (IPAH), chronic thromboembolic pulmonary hypertension (CTEPH), and acute pulmonary embolism (APTE) are life-threatening cardiopulmonary diseases without specific surgical or medical treatment. Although APTE, CTEPH and IPAH are different pulmonary vascular diseases in terms of clinical presentation, prevalence, pathophysiology and prognosis, the identification of their circulating microRNA (miRNAs) might help in recognizing differences in their outcome evolution and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In our DE analysis we detected the let-7 family members’ let-7a, let-7b, let-7c and let-7f to be downregulated in the patients. This was not the first time that members of this family were related to PAH, as let-7a had been reported to be downregulated under hypoxia and let-7f after monocrotaline treatment in a rat model [26], while the closely related let-7i-5p was upregulated in IPAH patients [27]. From this cluster, let-7b and let-7c did not show statistically significant downregulation in our prevalidation cohort, while let-7a and let-7f did so.…”
Section: Discussionmentioning
confidence: 99%
“…In our DE analysis we detected the let-7 family members’ let-7a, let-7b, let-7c and let-7f to be downregulated in the patients. This was not the first time that members of this family were related to PAH, as let-7a had been reported to be downregulated under hypoxia and let-7f after monocrotaline treatment in a rat model [26], while the closely related let-7i-5p was upregulated in IPAH patients [27]. From this cluster, let-7b and let-7c did not show statistically significant downregulation in our prevalidation cohort, while let-7a and let-7f did so.…”
Section: Discussionmentioning
confidence: 99%
“…The let-7 family has been demonstrated to be important in lung development and regulate RAS gene expression [ 22 ] . Fabro et al further reported that circulating miRNA-let-7i-5p significantly changed in patients with acute pulmonary embolism and idiopathic pulmonary arterial hypertension compared with healthy controls [ 23 ] . Let-7i-5p were just regulators of pulmonary arterial adventitial fibroblasts, pulmonary artery endothelial cells, and pulmonary artery smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…They have observed that transfection of let-7b-5p into HK-2 cells decreased the expression of IL-6, TNF-α, and IL-1β after LPS-induced inflammation 32 . Previous experimental studies suggested the role of miR-let-7b in suppressing tumors, which works by inhibiting tumor proliferation, invasion, and adhesion via interacting with various genes named HMGA2, RDX, DIAPH2, Ras c-myc, and PKA1 33 . let-7b-5p also downregulated the expression level of Suppressor of cytokine signaling 1 (SOCS1) and hiked the phosphorylation of STAT1, STAT5a, and STAT3 proteins in prostatic macrophages.…”
Section: Discussionmentioning
confidence: 99%